2012
DOI: 10.1039/c2ce06352b
|View full text |Cite
|
Sign up to set email alerts
|

A series of compounds forming polar crystals and showing single-crystal-to-single-crystal transitions between polar phases

Abstract: Condensation of 4-hydroxybenzohydrazide with a variety of non-chiral aliphatic ketones, methylethylketone, acetone, cyclohexanone and cyclobutanone, affords imine compounds crystallizing in polar space groups (Pna21 or Cc). For all the compounds synthesized, the crystal structure was determined by single crystal X-ray analysis and second harmonic generation experiments were performed on powder samples. The imine obtained using acetone shows solid state polymorphism with unusual behaviour; three different cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 46 publications
5
74
1
Order By: Relevance
“…Also, during the reversible phase transition, II ↔ III (both ways), crystals exhibited a jumping behaviour, although somewhat weaker than during the phase transition I to II. This is in contrast to previously reported behaviour [50] and the new model for jumping crystal phenomenon in this system has to be proposed. [51] A possible explanation of the thermosalient phenomenon may lie in the fact that a change of mutual positions of the molecules due to the change of temperature induced a severe stress in the crystal.…”
Section: Thermosalient Crystalscontrasting
confidence: 46%
See 1 more Smart Citation
“…Also, during the reversible phase transition, II ↔ III (both ways), crystals exhibited a jumping behaviour, although somewhat weaker than during the phase transition I to II. This is in contrast to previously reported behaviour [50] and the new model for jumping crystal phenomenon in this system has to be proposed. [51] A possible explanation of the thermosalient phenomenon may lie in the fact that a change of mutual positions of the molecules due to the change of temperature induced a severe stress in the crystal.…”
Section: Thermosalient Crystalscontrasting
confidence: 46%
“…It was also reported that during the irreversible phase transition from I to II, the polar axis undergoes a strong compression (approximately 15 %) and a single crystal of the phase I is violently shuttered into single crystal fragments of the phase II (without jumping), while in the reversible phase transition III to II the polar axis expands (approximately 14 %) and the integrity of the single crystals is preserved -and no movement of crystals was observed. [50] Our recent study ( Figures 13. and 14.) showed a different behaviour. [51] During the irreversible phase transition from I to II some of the crystals did indeed shutter into smaller fragments, but a large number remained intact and showed a typical jumping behaviour [49] -jumping all around over large distances (several cm).…”
Section: Thermosalient Crystalsmentioning
confidence: 99%
“…The properties such as ferroelectricity, piezoelectricity, and second-order optical nonlinearlity are allowed in a noncentrosymmetric structure. Other noncentrosymmetric SCSC transitions have been previously reported [14]. We discuss a possible mechanism for the enantiomorphic SCSC phase transition based on the crystal structure changes between the α-and β-forms.…”
Section: Resultsmentioning
confidence: 99%
“…The compound enol-(S)-1 was synthesized according to the literature procedure [14]. Single crystals were obtained by slow evaporation of the solution in 2-propanol at room temperature within several days.…”
Section: Methodsmentioning
confidence: 99%
“…29 This has been attributed to first order displacive solid-solid transition that occurs with Bain distortion. [38][39][40][41] Elastic properties in molecular solids are largely determined by the isotropy of crystal packing. 8,18 Recent studies by Ghosh and Reddy on caffeine co-crystals have established that bending of elastic organic crystals is related to isotropic packing with the presence of relatively weak and dispersive interactions in all directions.…”
Section: Introductionmentioning
confidence: 99%